Morphological analysis of the endemic freshwater halfbeak Dermogenys orientalis (Weber, 1894) in Maros Karst Region, South Sulawesi, Indonesia - MOH. TAUHID UMAR; SHARIFUDDIN BIN ANDY OMAR; ANDI ALIAH HIDAYANI; ACHMAD NABIL AL ASHAD; MUHAMMAD GAZALI; WIDYASTUTI UMAR; SAPTO ANDRIYONO; ANDI TENRIULO; ABIGAIL MARY MOORE (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Umar MT, Omar SBA, Hidayani AA, Ashad ANA, Gazali M, Umar W, Andriyono S, Tenriulo A, Moore AM. 2024. Morphological analysis of the endemic freshwater halfbeak Dermogenys orientalis (Weber, 1894) in Maros Karst Region, South Sulawesi, Indonesia. Biodiversitas 25: 3056-3066. The viviparous halfbeak Dermogenys orientalis is a freshwater fish endemic to the Maros-Pangkep Karst Region in South Sulawesi, Indonesia. Halfbeaks have a unique shape with a beak-like upper jaw considerably longer than the lower jaw. To date, research on the biology of this fish has been limited, in particular with respect to morphology. This study aims to analyze morphological (morphometric, and meristic) characteristics of D. orientalis populations in the Pattunuang, Bantimurung, and Leang-Leang rivers by sex. Morphological identification was carried out by comparing the morphology of fish originating from the Maros-Pangkep Karst Area based on the characteristics of the fish obtained and carried out in-situ. Morphometric analysis was performed using Stepwise Discriminant Analysis. Phenotypic distance between populations was inferred using Predicted Group Membership and Pairwise Group Comparison. Equality of Group Means Test was applied to discriminant morphometric traits and the t-test (?=0.05) to meristic traits. All statistical tests were performed using SPSS software version 22.0. The results showed that D. orientalis was sexually dimorphic and viviparous. In addition to the male andropodium, D. orientalis exhibited sexual dimorphism in body shape, and females were significantly longer (standard length) than males. The species characters identification found in this study were 13 and 19 characters for males and females respectively. The results of the t-test on the meristic character data that have been obtained, the mean values of three meristic traits (pectoral, anal and caudal fin ray counts) differed significantly between groups.